Spectroscopic Characterization of Eoholocene Bones Found in a Cave in Northeast Brazil - P. V. Oliveira; M. S. S. Viana; O. A. Barros; P. T. C. Freire; F. I. Bezerra; S. B. S. Gusmão; B. C. Viana; J. H. Silva (Journal of Spectroscopy)
The preservation of fossils depends on several interactions of organic and inorganic chemical processes. The hard parts, which are more suitable for fossilization, might record valuable information of biogenic processes, while the taphonomic characteristics supply information on postmortem chemical transformation. Here, X-ray fluorescence, X-ray diffraction, and infrared spectroscopy analyses were carried out in Early Eoholocene fragments of bones collected from the subsurface at Gruta do Urso Fóssil, Ubajara National Park, northeast of Ceará State in Brazil. It is suggested a lower degree of decomposition, a preservation of the original mineral composition, along with some incidence of encrustation, and the occurrence of different animal species are analyzed. These preliminary data serve as a basis for future studies involving fossil biota from the deposits of Gruta do Urso Fóssil using spectroscopic techniques.